Correlation between periodontal status, whole salivary interleukin-1beta levels and oral yeasts carriage among individuals with varying ranges of body mass index - Dena Ali; Toshinari Mikami; Fatema Alkazemi (Acta Odontologica Scandinavica)
Objective: The aim was to assess the correlation between periodontal status, whole salivary interleukin-1 beta (IL-1β) levels and oral yeasts carriage (OYC) among individuals with varying ranges of body mass index (BMI).